The interdisciplinary dilemmas of chronological criterion of old age – preliminary studies on older consumers - Bałandynowicz-Panfil, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In terms of researches on contemporary demographic changes, there are many methodological dilemmas. One of them is the old age criterion, adopted in different disciplines, as well as fields of a study. The subject of the paper is to analyze the differences of approaches to boundaries of senior age in an interdisciplinary perspective. The aim of the study is to answer the question: Who is, from a chronological point of view, an older person for economists, sociologists, demographers, and medicine. The base for that are literature studies, comparative analysis of methodology of previous empirical studies, as well as market practices. Next step is the attempt to specify the age cutoff in studies on seniors purchasing behaviors. The aim of this paper is to demonstrate the lack of consistency in the approach to the threshold of old age, both in specific disciplines as well as in relation to a narrower research area, which are older consumers. The current trend is very diverse (Bondos 2013: 31–36; OCCP 2009; Bombol, Słaby 2011; Stroud, Walker 2013; Gunter 1998). Older consumers are defined as persons aged over 50, 55, 60, or 65 years. The paper proves that the unified approach to this issue would allow for greater availability of comparative studies, statistics, and therefore more dynamic development of researches in the field of older consumers.